Incidence and Mortality of Bone Cement Implantation Syndrome after Hemi Arthroplasty: A Retrospective Analysis in a Single Institute of Karachi - Muhammad Hassam; Naseem Munshi; Athar Munir Ud Din Siddiqui; Muhammad Danish Ibrahim Baloch; Arif .; Arham Azizi (Life and Science)
Objective: To investigate the incidence and mortality associated with Bone Cement Implantation Syndrome following cemented hemiarthroplasty for femoral neck fractures. Study Design: Retrospective cohort study. Place and Duration of Study: The study was conducted at the Department of Orthopedics, Dr. Ziauddin Hospital, Karachi, Pakistan from 1st January 2022 to 31st December 2022. Methods: Patients who underwent cemented hemiarthroplasty at the Department of Orthopedics, Dr. Ziauddin Hospital, Karachi, Pakistan. The study included patients with complete medical records documenting cemented hemiarthroplasty as the primary treatment for femoral neck fractures. The incidence and severity of Bone Cement Implantation Syndrome were identified and categorized using established criteria. The association between 30-day mortality and Bone Cement Implantation Syndrome grade was analyzed using a two-tailed Fisher's exact test. Results: Out of 58 patients initially reviewed, 56 were included in the final analysis, with an observed incidence of Bone Cement Implantation Syndrome of 35.7% (20 patients). Among these, 5 patients exhibited severe Bone Cement Implantation Syndrome (grades 2 and 3). The analysis revealed no statistically significant association between the severity of Bone Cement Implantation Syndrome and 30-day mortality (P = 0.122). Demographically, 80.36% of the patients were male, with a median age of 76.5 years. Comorbidities included hypertension (64.29%) and diabetes (30.36%). Conclusion: Our study found a notable incidence of Bone Cement Implantation Syndrome remains a critical consideration in cemented hemiarthroplasty, its management does not significantly impact short-term mortality. Our findings underscore the importance of vigilant perioperative care and the potential benefits of larger Bone Cement Implantation Syndrome registries for improving patient outcomes.